Moderasi Beragama dan Ketahanan Sosial: Reaktualisasi Etika Pancasila dalam Masyarakat Multikultural - Ahmad Fathurrohman Syukri; Nurul Hidayati Marlina; Muhammad Salahuddin Wahid (Pancasila Spectrum: Jurnal Multidisiplin, 2026)
This study examines the relevance of Pancasila ethics as a foundation for religious moderation and social resilience in Indonesia's multicultural society. The background of this research lies in the increasing incidents of religious intolerance and social fragmentation that threaten national unity. The purpose is to reactualize Pancasila values as a guiding framework for interreligious harmony and multiculturalism. Using a qualitative approach with library research and discourse analysis methods, this study analyzes primary and secondary sources related to Pancasila philosophy, religious moderation policies, and social cohesion theories. The findings reveal that Pancasila's ethical principles particularly sila pertama and sila ketiga provide a robust normative basis for managing religious diversity and building social resilience. The study concludes that the reactualization of Pancasila ethics through education, policy, and community engagement is crucial for sustaining multicultural coexistence in contemporary Indonesia.